Developing the Strategic Sports Marketing Plan for the Lifeguard and Diving Federation in Islamic Republic of Iran - Meysam Rahimizadeh; Farideh Rezaei; Nahid Adibpour (Shahid Bahonar University of Kerman, 2023)
The purpose of this research is to develop a strategic marketing plan for the Lifeguard and Diving Federation of the Islamic Republic of Iran. The current research is a mixed study with the strategic approach. By conducting a combined method including expert opinion, review of valid documents, and using some matrices related to the formulation of a strategic plan, the formulation of a strategic plan for the marketing of the Lifeguard and Diving Federation has been discussed. The research participants included 15 members of the Board of Directors of the Lifeguard and Diving Federation, managers and sports marketing specialists. In quantitative phase, the measurement tool consisted of a researcher-developed questionnaire that was designed and adjusted using the Delphi method. According to the final score of the evaluation matrix of internal factors (2.47) and the evaluation matrix of external factors (2.44), it was determined that the strategic marketing position of Lifeguard and Diving Federation was in the WT position. The results of SWOT analysis have led to the formulation of 3 SO strategies, 3 ST strategies, 3 WO strategies, and 4 WT strategies. 13 strategies to fulfill the mission of the long-term marketing goals of the federation have been developed and an operational plan has been prepared for each of them. It was concluded that the lifeguard and diving federation needs to use defensive strategies and close to the competitive area (ST) in the field of action.